A new perspective for electrochemical determination of parathion and chlorantraniliprole pesticides via carbon nanotube-based thiophene-ferrocene appended hybrid nanosensor - Tumay, Sureyya Oguz; Senocak, Ahmet; Sari, Erdem; Sanko, Vildan; Durmuş, Mahmut; Demirbas, Erhan (Elsevier Science Sa, 2021)
The overuse of pesticides for agricultural activities causes adverse effects on human health and can lead to ecological pollution. Therefore, there has been a growing demand for accurate, sensitive, simple, and selective analytical methods for the determination of pesticide residues in food products, soil, etc. In this study, an electrochemical method was developed for the simultaneous determination of parathion and chlorantraniliprole pesticides based on novel electroactive and electropolymerizable group bearing hybrid nanomaterial. The novel hybrid ferrocene-thiophene modified by carbon nanotube (FT@CNT) was prepared by surface modification of the carbon nanotube with thiophene-ferrocene moieties via Click chemistry and used as an electrochemical nanosensor. The experimental conditions such as pH and concentration of the nanosensor were optimized prior to the electrochemical determination of parathion and chlorantraniliprole pesticides in tomatoes, apples and soil samples. The LODs for parathion and chlorantraniliprole in the linear range of 0.02-6.50 mu mol/L and 0.01-7.00 mu mol/L were determined as 5.3 nmol/L and 8.1 nmol/L, respectively. The accuracy of the electrochemical methods was evaluated by spike/recovery and HPLC analysis in food and soil samples. The comparison between the electrochemical method and other analytical techniques for the determination of pesticides revealed that the electrochemical methods were not only easy to operate and fast but also highly sensitive and selective for the simultaneous determination of parathion and chlorantraniliprole residues in food and soil samples. The hybrid material demonstrated excellent stability and high sensitivity towards parathion and chlorantraniliprole pesticides.
Keywords: Chlorantraliprole; Parathion; Thiophene; Ferrocene; Carbon nanotubes; Hybrid material; Electrochemical nanosensor; Pesticide determination